2019
DOI: 10.1093/mnras/stz3137
|View full text |Cite
|
Sign up to set email alerts
|

Active galactic nuclei winds as the origin of the H2 emission excess in nearby galaxies

Abstract: In most galaxies, the fluxes of rotational H 2 lines strongly correlate with star formation diagnostics (such as polycyclic aromatic hydrocarbons, PAH), suggesting that H 2 emission from warm molecular gas is a minor byproduct of star formation. We analyse the optical properties of a sample of 309 nearby galaxies derived from a parent sample of 2,015 objects observed with the Spitzer Space Telescope. We find a correlation between the [O i]λ 6300 emission-line flux and kinematics and the H 2 S(3) 9.665 µm/PAH 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 122 publications
0
12
0
Order By: Relevance
“…Krug et al 2010;Rupke & Veilleux 2011;Cazzoli et al 2016;Concas et al 2019;Roberts-Borsani 2020), cold molecular gas phase, using different transitions of CO, HCN and [C ii], for instance (e.g. García-Burillo et al 2014;Tadhunter et al 2014;Feruglio et al 2017;Aladro et al 2018;Michiyama et al 2018;Zschaechner et al 2018;Aalto et al 2019;Husemann et al 2019;Cicone et al 2020;Veilleux et al 2020), warm and hot molecular gas phase, using transitions in the mid-to near-infrared (Veilleux et al 2009;Davies et al 2014;Hill & Zakamska 2014;Riffel et al 2015;Emonts et al 2017;May et al 2018;Petric et al 2018;Riffel et al 2020) and ionised gas phase observed using the rest-frame optical emission lines such as the forbidden transitions of [O iii] λ5007 (e.g. Harrison et al 2014;Kakkad et al 2016;Zakamska et al 2016;Fiore et al 2017;Venturi et al 2018;Baron & Netzer 2019;Coatman et al 2019;Förster Schreiber et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Krug et al 2010;Rupke & Veilleux 2011;Cazzoli et al 2016;Concas et al 2019;Roberts-Borsani 2020), cold molecular gas phase, using different transitions of CO, HCN and [C ii], for instance (e.g. García-Burillo et al 2014;Tadhunter et al 2014;Feruglio et al 2017;Aladro et al 2018;Michiyama et al 2018;Zschaechner et al 2018;Aalto et al 2019;Husemann et al 2019;Cicone et al 2020;Veilleux et al 2020), warm and hot molecular gas phase, using transitions in the mid-to near-infrared (Veilleux et al 2009;Davies et al 2014;Hill & Zakamska 2014;Riffel et al 2015;Emonts et al 2017;May et al 2018;Petric et al 2018;Riffel et al 2020) and ionised gas phase observed using the rest-frame optical emission lines such as the forbidden transitions of [O iii] λ5007 (e.g. Harrison et al 2014;Kakkad et al 2016;Zakamska et al 2016;Fiore et al 2017;Venturi et al 2018;Baron & Netzer 2019;Coatman et al 2019;Förster Schreiber et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The warm (T ∼ 500 K) molecular gas phase may also be important and carry a significant fraction of the momentum in a galactic outflow (Richings & Faucher-Giguère 2018). In nearby galaxies, Spitzer observations of the warm molecular H 2 gas (T ∼ 500 K) have found a significant amount of gas mass in galactic outflows (Dasyra et al 2014;Beirão et al 2015;Riffel et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ellison et al 2019), so if the time-scales for shocked H 2 gas are similar to those of AGN then the statistics of shocked H 2 gas should change with AGN triggering mechanism because different AGN triggering could lead to different gas motions and properties. Riffel et al (2020) use SDSS optical spectra for a subsample of the Lambrides et al (2019) galaxies to suggest that excess of MIR H 2 emission seen in AGN is produced by shocks due to AGN driven outflows in the same clouds that produce [OI] emission. Spatially resolved kinematics would be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%